The magnification of endemic construction industry problems in the implementation of mega projects in South Africa - Moalusi, Pearl Nozuko (My University, 2019)
This study aims to identify and investigate the extent of magnification of the endemic construction industry implementational problems in the mega projects within South Africa. South Africa has shown a great deal of interest in mega construction projects to become more economically and socially advanced. South African Government has adopted Mega Construction Projects to upgrade dilapidated infrastructure, as a speedy delivery mode to address the housing backlog and create mega cities. The implementation of Mega Projects in South Africa has been followed by a plethora of problems which causes delays in the delivery of MCP. This research undertook descriptive research which adopted a mixed methodology strategy based on cross ‐ sectional survey of six registered Project Managers with the South African Council for Project, two registered Consulting Engineers with Engineering Council of South Africa (ECSA), one registered Architect with South African Council of Architectural Profession (SACAP) and seventeen non – registered Project Managers, Professional Resource Teams(PRT) registered within the Gauteng Human Settlement database using questionnaires distributed by email. Total number of 26 were distributed to 12 registered PM, 4 Consulting Engineers, 1 Architect and 8 non‐ registered PM and 25 responded. The endemic problems identified with implementation of mega projects and normal projects were time and cost overruns, stakeholder mis‐ management and unforeseen conditions. The research revealed that in the South African construction industry 72% of the practitioners indicated that the identified problems are magnified in mega projects. 60% respondents showed that cost and time overruns are magnified in mega projects by double to triple which causes delay in the delivery of project objectives. In normal projects, problems are less magnified as they would not exceed 50% of the initial budget and time of the project. Findings based on the respondents, has revealed that MP encounter excessive cost and time overruns due to unforeseen conditions as critical factor that impedes successful delivery of MP in South Africa. An in‐depth cost estimate is minimal at the planning stage of projects. This can be accomplished by developing realistic cost estimate model / tool that can overcome the excessive cost overruns. This proposed tool can be utilised at the planning stage of a project to identify and plan all possible unforeseen conditions to maximise all possibilities to meet project objectives within the set time and cost. Lastly, it is recommended that South African Government enforces integrated governmental relations and community engagement through constant consultation to meet project objectives.
A research report submitted to the Faculty of Engineering and the Built Environment, University of Witwatersrand, in the fulfillment of the requirements for the degree of Master of Science in Building (Project Management). BUQS7027 October 2019
Keywords: Project management; Construction projects; Construction projects--Environmental aspects